First-year university Physics students' knowledge about direct current circuits: probing improvement in understanding as a function of teaching and learning interventions. (11th May 2017) - Newman, Richard; van der Ventel, Brandon; Hanekom, Crischelle
Abstract: Probing university students' understanding of direct-current (DC) resistive circuits is still a field of active physics education research. We report here on a study we conducted of this understanding, where the cohort consisted of students in a large-enrollment first-year physics module. This is a non-calculus based physics module for students in the life sciences stream. The study involved 366 students enrolled in the physics (bio) 154 module at Stellenbosch University in 2015. Students' understanding of DC resistive circuits was probed by means of a standardized test instrument. The instrument comprises 29 multiple choice questions that students have to answer in 40 min. Students were required to first complete the standardized test at the start of semester (July 2015). For ease of reference we call this test the pre-test. Students answered the pre-test having no university-level formal exposure to DC circuits in theory or practice. The pre-test therefore served to probe students' school level knowledge of DC circuits. As the semester progressed students were exposed to a practical (E1), lectures, a prescribed textbook, a tutorial and online videos focusing on DC circuits. The E1 practical required students to solve DC circuit problems by means of physically constructing circuits, algebraically using Kirchhoff's Rules and Ohm's Law, and by means of simulating circuits using the app iCircuit running on iPads (iOS platform). Each E1 practical involved 50 students in a three hour session. The practical was repeated three afternoons per week over an eight week period. Twenty three iPads were distributed among students on a practical afternoon in order for them to do the circuit simulations in groups (of 4–5 students). At the end of the practical students were again required to do the standardized test on circuits and complete a survey on their experience of the use of the iPad and iCircuit app. For ease of reference we refer to this second test as the post-test. The students' average score on the post-test was found to be 25% higher than their pre-test score. The results of the iPad use survey show that the majority of students felt that the iCircuit app enhanced their learning of DC circuits.